Enrique Ramírez - Los durmientes - Cifuentes, Guillermo 1968-; Escobar, Ticio 1947-; Olhagaray, Néstor; Davenne, Coline; Battiti, Florencia (Ediciones Metales Pesados, 2018)
Addressing pain, absence and terror, and to do it poetically, is not simple for a visual artist. To revisit the past with good will or a fierce political commitment is not enough to build a body of work that will move people, and also pose questions to reactivate the past critically and poetically. Usually, slapping a sleeping consciousness with bursts of expressivity and wrath does not yield good results. When horror presents itself as a mirror, without any mediation, without any metaphors, the work will not garner the spectators empathy and he or she, irremediably, will withdraw, hide or escape. Quite on the contrary, the work of Enrique Ramírez is a balm, suggestive, without renouncing the necessary dose of discomfort and perplexity that questions the common place, the certainties and, even, the prejudice about the artistic production that alludes the recent past.
"This book has been published on the occasion of the exhibitions: "Los Durmientes", 20 de octubre a 23 de noviembre 2014, premio 'amis Palais de Tokyo', Paris, Francia. "Brisas", 23 de julio al 11 de septiembre, 2009, Galeria Gabriela Mistral. ; "Los Durmientes: el exilio imaginado", 23 de abril a 23 de agosto, 2015, Museo de la Memoria y los Derechos Humanos, Santiago de Chile ; "Los Durmientes: encuentros latinoamericanos n 1, El tiempo, el ámbito, el mundo", 17 de octubre de 2015 a 8 de febrero de 2016, curada por Angeles Alonso, Museo Amparo, Puebla México. ; "Los Durmientes", 26 de junio al 17 de julio, 2016, Espacio HLM, Marsella, Francia. ; "Los Durmientes: mar dulce", 29 de marzo al 14 de mayo 2016, Centro Cultural MATTA, Embajada de Chile en Argentina"--Page [170]
Keywords: Ramírez, Enrique -- 1979-; Ramírez, Enrique / 1979- / Exhibitions; Ramírez, Enrique / 1979- / Criticism and interpretation; Video art / Chile / Exhibitions; Installations (Art) / Chile / Exhibitions; Art, Chilean / Themes, motives; Installations (Art); Video art; Chile; 2000-2099; Criticism, interpretation, etc; Exhibition catalogs; Ausstellungskatalog -- Palais de Tokyo -- 20.10.2014-23.11.2014 -- Paris; Ausstellungskatalog -- Galería Gabriela Mistral -- 23.07.2009-11.09.2009 -- Santiago de Chile; Ausstellungskatalog -- Museo de la Memoria y los Derechos Humanos -- 21.04.2015-23.08.2015 -- Santiago de Chile; Ausstellungskatalog -- Museo Amparo -- 17.10.2015-08.02.2016 -- Puebla, Stadt; Ausstellungskatalog -- Espacio HLM -- 26.06.2015-17.07.2015 -- Marseille; Ausstellungskatalog -- Centro Cultural MATTA -- 29.03.2016-14.05.2016 -- Buenos Aires; Bildband